Trends in Tonnage: A Century of Lake Superior Shipping - Abplanalp, Kelly; Cox, Tom; Rooney, Tim; Nguyen, Sunny (My University, 2013)
Over the past century, Lake Superior shipping has varied immensely. The product of our research is a dynamic cartographic visualization that presents tonnage, population, and historical data for seven Lake Superior ports and the Sault-Saint Marie Canals. The significance of shipping to the success or failure of port towns cannot be underestimated, and many factors including infrastructure, economy, and local resources impact the extent of ports? ability to export. By juxtaposing visual representation of tonnage and pertinent information such as historical context and population, one can discover reasons for the increases and decreases in shipping history, be them economically related or due to specific historical events. This interface allows users to explore shipping fluctuations and draw their own conclusions regarding the data through the use of a proportional symbol map and accompanying bar graphs.
Includes Maps, Figures, Appendix and Bibliography.
Keywords: Lake Superior; Shipping